Dietary quercetin improved the growth, antioxidation, and flesh quality of grass carp (Ctenopharyngodon idella). Issue 6 (25th October 2019) - Xu, Zhen; Li, Xiaoqin; Yang, Hang; Liang, Gaoyang; Gao, Bowei; Leng, Xiangjun
Abstract: To investigate the effects of dietary quercetin on growth, antioxidation, and flesh quality of grass carp, Ctenopharyngodon idella, six diets were prepared with quercetin inclusion rates of 0 (control diet), 0.1, 0.2, 0.4, 0.6, and 0.8 g/kg. Grass carp with a body weight of 13.3 ± 0.1 g were fed with one of the six diets for 60 days. The weight gain (WG) showed a quadratic relationship with dietary quercetin levels; the supplementation of 0.4 g/kg quercetin significantly improved WG (+4.73%) and decreased feed conversion ratio (−0.06) ( p < .05) when compared to those of the control group. The intestinal fat ratio was reduced by the addition of 0.2 or 0.4 g/kg of quercetin ( p < .05), and serum activities of alkaline phosphatase and superoxide dismutase were increased by the addition of 0.4 and 0.6 g/kg of quercetin ( p < .05). The inclusion of 0.2–0.6 g/kg of quercetin increased the contents of delicious amino acids and decreased the cooking loss of flesh ( p < .05). Flesh collagen content was increased by the addition of 0.4–0.8 g/kg of quercetin ( p < .05). In conclusion, dietary quercetin could improve the growth and enhance the antioxidation and flesh quality of grass carp, with the recommended supplemental level of quercetin was 0.37 g/kg.